Evaluation of the mining potential of the São Domingos mine wastes, Iberian Pyrite Belt, Portugal - Vieira, Alexandre (2020)
Abstract: The outcropping São Domingos Iberian Pyrite Belt deposit was mined since Roman time and between 1857 and 1966. The mine is formed by a 120 m depth flooded open pit and galleries until 420 m depth. Associated with felsic volcanic rocks and black shales of the Volcano-Sedimentary Complex, the deposit is formed by massive sulphide and stockwork ore (py, ccp, sp, ga, tt, apy) and related supergene enrichment ore (hematite gossan and covellite/chalcocite). Different mine wastes classes were mapped: gossan, felsic volcanic and shales, shales and landfill. Considering the CONASA mining waste characterization (162 shafts and 160 reverse circulation boreholes/LNEG database), new inferred resources are presented, using block modelling software: 2.38 Mt @ 0.77 g/t Au and 8.26 g/t Ag in non-conditioned volumes. Considering all evaluated wastes, including urban areas, an inferred resource of 4.0 Mt @ 0.64 g/t Au and 7.30 g/t Ag is presented, corresponding to a metal content of 82,878 oz t Au and 955,753 oz t Ag. Keywords: São Domingos mine, mining wastes resources, Iberian Pyrite Belt.